Peran Akademis dalam Mengangkat Citra dan Pemasaran Kue Tradisional Podeng Produk Asli Tigaraksa - Dede Puspa Pujia; Susilowati Susilowati; Hurian Kamela; Cecep Edi Hidayat; Rabitha Fazira; Wati Yaramah (Jurnal Pengabdian Masyarakat, 2025)
Traditional cakes are an important part of the history of a region that has always been a valuable attraction and has great potential in supporting the local economy if managed and developed properly. Therefore, there needs to be attention from academics in advancing traditional cake entrepreneurs, as done by Lecturers and Students conducting Community Service Activities (PKM) where the partners are traditional cake entrepreneurs from Sodong Village, Tigaraksa, Tangerang Regency. This Community Service Activities (PKM) aims to provide an introduction to marketing and financial management order to improve the image and marketing of traditional Podeng cakes, original Tigaraksa products. The results of this Community Service Activity are that traditional Podeng cake entrepreneurs can improve product packaging to be more modern, neat, attractive and can record finances with simple accounting. Traditional Podeng cake entrepreneurs are very enthusiastic about this activity, as can be seen from the very interactive activities between the speakers and partners.